Pharmacological Targeting of STING-Dependent IL-6 Production in Cancer Cells - Al-Asmari, Sumaiah S.; Rajapakse, Aleksandra; Ullah, Tomalika R.; Pépin, Geneviève; Croft, Laura V.; Gantier, Michael P. (Frontiers in Cell and Developmental Biology, 2022)
Activation of the STING pathway upon genotoxic treatment of cancer cells has been shown to lead to anti-tumoral effects, mediated through the acute production of interferon (IFN)-b. Conversely, the pathway also correlates with the expression of NF-κB-driven pro-tumorigenic genes, but these associations are only poorly defined in the context of genotoxic treatment, and are thought to correlate with a chronic engagement of the pathway. We demonstrate here that half of the STING-expressing cancer cells from the NCI60 panel rapidly increased expression of pro-tumorigenic IL-6 upon genotoxic DNA damage, often independent of type-I IFN responses. While preferentially dependent on canonical STING, we demonstrate that genotoxic DNA damage induced by camptothecin also drove IL-6 production through non-canonical STING signaling in selected cancer cells. Consequently, pharmacological inhibition of canonical STING failed to broadly inhibit IL-6 production induced by CPT, although this could be achieved through downstream ERK1/2 inhibition. Finally, prolonged inhibition of canonical STING signaling was associated with increased colony formation of MG-63 cells, highlighting the duality of STING signaling in also restraining the growth of selected cancer cells. Collectively, our findings demonstrate that genotoxic-induced DNA damage frequently leads to the rapid production of pro-tumorigenic IL-6 in cancer cells, independent of an IFN signature, through canonical and non-canonical STING activation; this underlines the complexity of STING engagement in human cancer cells, with frequent acute pro-tumorigenic activities induced by DNA damage. We propose that inhibition of ERK1/2 may help curb such pro-tumorigenic responses to DNA-damage, while preserving the anti-proliferative effects of the STING-interferon axis.